Existence of nodal solutions to some nonlinear boundary value problems for ordinary differential equations of fourth order - Ziyatkhan Aliyev; Yagut Aliyeva (Electronic Journal of Qualitative Theory of Differential Equations)
In this paper, we study the existence of nodal solutions of some nonlinear boundary value problems for ordinary differential equations of fourth order with a spectral parameter in the boundary condition. To do this, we first study the global bifurcation of solutions from zero and infinity of the corresponding nonlinear eigenvalue problems in classes with a fixed oscillation count. Then, using these global bifurcation results, we prove the existence of solutions of the considered nonlinear boundary value problems with a fixed number of nodes.